DiGeorge Syndrome Presenting as Hypocalcaemia-Induced Seizures in Adulthood - Adrian Zammit; Deborah Grech Marguerat; Josephine Psaila; Alexander Attard (Case Reports in Medicine)
Introduction. DiGeorge syndrome is a developmental defect commonly caused by a microdeletion on the long arm of chromosome 22 or less frequently by a deletion of the short arm of chromosome 10. Case report. We report a case of a gentleman with mild dysmorphic features who presented with hypocalcaemia-induced seizures and an associated thyroid mass with a background of learning difficulties and abnormal immune function. Discussion. DiGeorge syndrome was initially described in 1967 by Angelo DiGeorge. The majority of cases are due to a novel mutation. The resulting learning difficulties, congenital heart disease, palatal abnormalities, hypoplasia/aplasia of the parathyroid and thymus glands, and immune deficiency generally lead to diagnosis in childhood. Presentation in adulthood is rare but must be borne in mind when dealing with cases of hypocalcaemia even in the absence of florid phenotypic features. A link with malignant disease has also been reported and should lead to prompt investigation of concerning masses.